HUBUNGAN PERSEPSI TENTANG MUTU PELAYANAN DENGAN MINAT KUNJUNGAN ULANG PASIEN RUMAH SAKIT ROYAL PRIMA JAMBI - Pairi, Agus; Ginting, Marinawati; Silitonga, Sondang (SCIENTIA JOURNAL, 2018)
Government policy regarding national health insurance (JKN) has triggered an increase in the growth of the health services sector, where JKN has provided broad opportunities for Indonesians to access health services. As an impact, there was an over demand so that the development of the hospital industry experienced a rapid growth and almost all hospitals participated in